Detecting the hidden burden of pre-diabetes and diabetes in Western Sydney. (May 2019) - Meyerowitz-Katz, Gideon; Seelan, Shanthini; Gaur, Pankaj; Francisco, Rona; Ferdousi, Shahana; Astell-Burt, Thomas; Feng, Xiaoqi; Colagiuri, Stephen; Maberly, Glen; Hng, Tien-Ming
Highlights: Opportunistic testing in EDs and GPs is feasible for identifying patients with diabetes. Surprisingly high rates of diabetes exist in tested patients at both ED and GP. This has implications for diabetes policy and testing practice guidelines. Abstract: Aims: Examining pre-diabetes and diabetes rates using glycated haemoglobin (HbA1c ) in emergency department (ED) and in general practice (GP) in western Sydney. Methods: Epidemiological study of HbA1c measurements in individuals ≥18 years receiving a blood test (1) in the hospital setting of the ED at Blacktown/Mt Druitt hospital (1/06/2016 to 31/05/2018) and (2) in primary care involving Bridgeview Medical Practice (BVMP) (1/03/2017 to 01/02/2018) as well as other general practices (June 2018 only). Results: Totals of 55, 568 individuals from ED and 5911 individuals from GP. The prevalence of diabetes in tested individuals was 17.3% (n = 9704) in ED and 17.4% (n = 1027) in GP. The prevalence of pre-diabetes in ED was 30.2% (n = 16, 854) and 26.6% (n = 1576) in GP. Regression controlling for age, season, and gender revealed a weekly increase of 1.1% in odds for diabetes and 1.5% for pre-diabetes (p < 0.001), in line with the yearly absolute increase of 1% in rate for both tested and coded hospital patients. In BVMP the rate of diabetes rose by 22% during the testing period from 8.9% to 11%. Conclusions: There exists a high burden of diabetes both in hospitals and general practice. Testing in ED and general practice revealed similarly high burdens of diabetes across different areas of the healthcare system. In the appropriate hospital and primary care setting, HbA1c can be used to identify individuals with diabetes that may benefit from targeted intervention.